Anthropology and Sociology as Lenses of Analysis: Islamic Practices in the Modern Era - Muhammad Habibi Perdana; Achmad Sulton (Values: Jurnal Kajian Islam Multidisiplin, 2026)
This study aims to understand Islamic practices in the modern era as a social phenomenon shaped by changes in technology, culture, and social structure. Modernity, globalization, and the development of digital media have created new ways for Muslims to express, understand, and practice their religion in everyday life. The research uses a qualitative approach with a socio-religious ethnographic design that combines anthropological and sociological perspectives. Data were collected through participant observation, documentation of religious practices, and analysis of digital media and relevant academic sources. The analysis was conducted thematically and interpretatively to understand the meaning of religious practices within their social and cultural contexts. The findings show that contemporary Islamic practices are increasingly diverse, flexible, and connected to digital technology, while still shaped by local culture and social structures. Religious authority has become more open, and religious identity is increasingly integrated with modern lifestyles. The discussion indicates that changes in religious practice occur through processes of adaptation and negotiation between tradition and modernity, allowing Islamic practice to continue developing as a dynamic and lived social experience in contemporary society.